HUBUNGAN BODY IMAGE DENGAN SELF-PRESENTATION PADA DEWASA AWAL PENGGUNA INSTAGRAM - Simon, Sevilla; Agustina, Agustina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Instagram, as a visual-based social media platform, encourages users to present themselves attractively, often influenced by their perception of body image. This study aims to examine the relationship between body image and self-presentation among young adult Instagram users. A total of 263 participants aged 18–25 were selected through purposive sampling. The instruments used were the Multidimensional Body-Self Relations Questionnaire (MBSRQ) to measure body image and the Presentation of Online Self Scale (POSS) to measure self-presentation. Data analysis using Spearman's correlation revealed a significant negative relationship between body image and self-presentation (? = –0.371, p < 0.001). This indicates that individuals with a more positive body image tend to engage less in intense and inauthentic self-presentation on social media. These findings suggest that a positive body perception plays an important role in shaping a more authentic digital self. The study highlights the importance of promoting healthy body image education to support more mindful and balanced use of social media among young adults. ABSTRAK Instagram sebagai media sosial visual mendorong penggunanya untuk menampilkan diri secara menarik, sering kali dipengaruhi oleh persepsi terhadap tubuh atau body image. Penelitian ini bertujuan untuk mengetahui hubungan antara body image dan self-presentation pada dewasa awal pengguna Instagram. Sebanyak 263 partisipan berusia 18–25 tahun dipilih melalui teknik purposive sampling. Instrumen yang digunakan adalah Multidimensional Body-Self Relations Questionnaire (MBSRQ) untuk mengukur body image dan Presentation of Online Self Scale (POSS) untuk mengukur self-presentation. Analisis data menggunakan korelasi Spearman menunjukkan hubungan negatif yang signifikan antara body image dan self-presentation (? = –0.371, p < 0.001). Artinya, semakin positif body image individu, semakin rendah kecenderungan mereka menampilkan diri secara intens dan tidak autentik di media sosial. Temuan ini menunjukkan bahwa persepsi positif terhadap tubuh berperan dalam membentuk representasi diri yang lebih autentik. Implikasi penelitian ini menggarisbawahi pentingnya edukasi terkait body image sehat untuk mendorong penggunaan media sosial yang lebih sadar dan seimbang.